Design of LMI+I controller based in optimization for two degree of Freedom Helicopter - Higuera-Martínez, Oscar Iván; Salamanca, Juan Mauricio (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2007)
Its presents the Genetic Algorithms' use for the design's  optimization of a Robust control H8 using lineal Matrix Inequalities' techniques,  to control pitch and  yaw's  position in a two degrees of freedom helicopter. The optimization is carried out when the pitch and  yaw's speed sensor, based on the energy consumption fails, the maximum peak and oscillation frequency of the system. The simulations'  results are presented on the non-linear model system.